Effects of rutin on laying performance, egg quality, serum biochemistry, antioxidant capacity and immunity in laying hens fed a diet containing stored soybean meal - Hengzhi Li; Rui Jin; Yunfeng Gu; Mingfang Du; Yanmin Zhou (Italian Journal of Animal Science)
This study aimed to investigate the effects of rutin on laying performance, egg quality, serum biochemical parameters, serum immunoglobulin, and antioxidant status in laying hens fed a diet containing stored soybean meal (SBM). The dietary treatments used were arranged in a 2 × 2 factorial arrangement with 2 types of SBM (FSM: SBM was stored in the cold storage warehouses at −20 °C for 45 days and was considered as fresh SBM; RTSM: SBM was stored in room temperature warehouse (15 °C to 25 °C), average temperature was 20 °C for 45 days) and 2 levels of rutin (0 and 500 mg/kg). In total, 384 Hy-Line Brown laying hens (220 days of age) were randomly divided into 4 groups with eight replicates. Pre-feeding period was 1 week, and the experiment lasted for 8 weeks. The results showed that the RTSM diet had no effect on laying performance (p > 0.05). Compared with the diet without rutin, diet with 500 mg/kg rutin exhibited a tendency to increase egg mass compared with the diet without rutin (p = 0.096), and there was a trend of interaction effect on average egg weight (p = 0.061). The RTSM diet decreased the egg Haugh unit significantly compared with the FSM diet at the end of 8th week (p < 0.05). Compared with the diet without rutin, dietary rutin supplementation could affect egg quality as evidenced by increased eggshell thickness, albumen height, egg yolk colour at the end of 4th week and increased eggshell strength and eggshell thickness at the end of 8th week (p < 0.05). Furthermore, dietary rutin supplementation increased urea nitrogen, decreased the immunoglobulin M (IgM) content in serum compared with the diet without rutin (p < 0.05). Compared with the diet without rutin, dietary supplementation with rutin improved the total antioxidant capacity in the serum and liver (p < 0.05). The interactions of SBM × Rutin were observed on egg yolk ratio at the end of 8th week, and the urea nitrogen and IgM content in serum. These findings suggested that diet with RTSM had adverse effects on egg quality in laying hens. The RTSM diet negatively impacted egg quality of laying hens over time when compared to the FSM diet. Dietary rutin supplementation could improve the egg quality, and antioxidant capacity of laying hens.